2016
DOI: 10.1111/ans.13842
|View full text |Cite
|
Sign up to set email alerts
|

Mini C‐arm: faster, cheaper, safer?

Abstract: The Fluoroscan mini C-arm II does not demonstrate a radiation saving during closed reductions of paediatric forearm fractures but allows shorter procedures and theatre time with similar re-displacement rates. The purchase price is lower than a traditional II. We noted that operator experience reduces radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Due to its smaller size and overall practicality, the mini C-arm could be a suitable choice to solve the problem of difficult movement (13,14). Gieroba TJ et al demonstrated that since the surgeon can easily operate mini C-arm without a radiographer, it reduces surgery delays and saves about 4 minutes of operation time per surgery (15). Although the mini C-arm fluoroscopy device has been promoted mainly due to its easy mobility, decreased cost, and its usage in taking images from smaller parts of the body in the operation room or emergency department (16,17), recently van Rappard JRM et al indicated that the image quality is significantly better for the mini C-arm in comparison with the standard C-arm in hand surgeries (18).…”
Section: Physical Aspectmentioning
confidence: 99%
“…Due to its smaller size and overall practicality, the mini C-arm could be a suitable choice to solve the problem of difficult movement (13,14). Gieroba TJ et al demonstrated that since the surgeon can easily operate mini C-arm without a radiographer, it reduces surgery delays and saves about 4 minutes of operation time per surgery (15). Although the mini C-arm fluoroscopy device has been promoted mainly due to its easy mobility, decreased cost, and its usage in taking images from smaller parts of the body in the operation room or emergency department (16,17), recently van Rappard JRM et al indicated that the image quality is significantly better for the mini C-arm in comparison with the standard C-arm in hand surgeries (18).…”
Section: Physical Aspectmentioning
confidence: 99%